The Effect and Mechanism of TLR9/KLF4 in FFA-Induced Adipocyte Inflammation - Cuizhe Wang; Meixiu Zhang; Jinxiu Wu; Wei Li; Xiaodan Ha; Yajuan Gu; Bo Han; Jianxin Xie; Jun Zhang (Mediators of Inflammation)
Objective. Current research has reported that obesity is a chronic inflammatory state, which is closely related with excessive accumulation of free fatty acid, while the specific mechanism that high level of FFA causes inflammation is not very clear. Thus, our research intended to observe the high FFA effects on TLR9/KLF4 expression and the downstream inflammatory factors, to explore the mechanism of inflammatory response suppressed by TLR9/KLF4. Methods. qRT-PCR and Western blot were used to detect the mRNA and protein expression levels of TLR9, KLF4, and key inflammation-related factors. ELISA was used to detect the release level of inflammatory cytokines. The triglyceride (TG) and glucose (GLU) testing cassettes were used to detect the TG and GLU levels in culture medium. Results. In the omental tissue of obese individuals (OB), we found that TLR9, KLF4, mRNA, and the protein expression levels were lower than those of the normal weight control (NC) group. Similarly, in the omental tissue of high-fat diet (HFD) rats, we found that the mRNA expression levels of TLR9 and KLF4 were lower than those of the normal diet control group. In mature adipocytes, we found that KLF4 played an important anti-inflammatory role; moreover, PA can promote the development of inflammation by inhibiting KLF4 expression; TLR9 has a positive regulation function on KLF4 expression, but unrelated to PA. Conclusions. TLR9/KLF4 is involved in regulating FFA-induced adipocyte inflammation.